PENGARUH PEMBERIAN PAKAN KONSENTRAT DAN UREA MOLASES BLOK (UMB) TERHADAP HEMOGLOBIN SAPI POTONG - Syam, Jumriah; Tolleng, A.L; Umar, Umar (Teknosains: Media Informasi Sains dan Teknologi, 2016)
This study aims to find out how the effect of feed concentrate and the urea molasses block (UMB) to hemoglobin beef cattle. Riset in Samata Farming Integrated Systems (FIS) Gowa Regency and Lab. Integrated Livestock Product Technology, Faculty of Science and Technology UIN Alauddin Makassar. The method used a randomized block design (RAK) with 2 x 6 pattern, (T1; forage 70 + concentrate 30%), (T2; forage 70 + UMB 30%), using as 12 heads of bali cattle. Data analysis using t-student. The results showed that the concentrate and the urea molasses block (UMB), was not significant (P> 0.05) to the hemoglobin value of beef cattle.